Weather Conditions (with Focus on UV Radiation) Associated with COVID-19 Outbreak and Worldwide Climate-based Prediction for Future Prevention - Lucian Sfîcă; Mihai Bulai; Vlad-Alexandru Amihăesei; Constantin Ion; Marius Ștefan (Aerosol and Air Quality Research)
Abstract Respiratory infectious diseases are highly influenced by climate and feature seasonality, whose peak is December to February in the Northern Hemisphere. SARS-CoV-2 produced consistent debate regarding the relationship between its emergence and weather conditions. Our study explored these conditions, expressed by three main parameters—ultraviolet radiation, air temperature and relative humidity—that characterized Hubei (China), the source region of COVID-19 pandemic, in November 2019–March 2020. During COVID-19 outbreak, the low amounts of UV radiation (down to –273 kJ m−2 in January 2020) were associated with the early stage environmental survival of the novel coronavirus. As well, this period was characterized by a high relative humidity during peak hours of the day, and a positive air temperature anomaly (+1.7°C in December 2019), which also favored the outdoor people mobility in winter. Based on Hubei analysis, a presumed optimal weather frame was set in order to identify other world regions with similar weather characteristics. In brief, the „Hubei weather profile” was recorded in those regions of COVID-19 outbreak in February 2020, such as northern Iran, Italy or Spain. Our results, which focused on the role of the UV solar radiation, could be used as a prediction tool for identifying the world regions with a higher risk of future faster increase in COVID-19 cases.